PERKEMBANGAN POPULASI KEPIK (Nesidiocoris tenuis DAN Lygus sp.) PADA TANAMAN KENTANG DI DESA LINELEAN KECAMATAN MODOINDING - Ester . Kotambunan; Max . Tulung; Daisy . Kandowangko; Juliet M.E. Mamahit (Universitas Sam Ratulangi, 2013)
ABSTRACTPotato (Solanum tuberosum L.) is one of the important vegetable commodities that have great potential to support food diversification program. . Besides the development of the snack industry and fast food restaurants are one of the raw material is potato thus increasing the demand for potato products both in quantity and quality that is safe for consumption. This study aims to determine the population growth miridae (Nesidiocoris tenuis and Lygus sp) on potato in Linelean Village District Modoinding. The research took place for two months from May to July 2012. Observations development of populations miridae (N. tenuis and Lygus sp.) Executed directly on the potato crop by counting the number of individuals per plant nymph and imago. Observations were carried out 5 times since 3 weeks old plants at intervals of 2 weeks is 3 (wap), 5 (wap), 7 (wap), 9 (wap), and 11 (wap). Each observation was observed 20 samples with random sampling method. The results showed the populations N. tenuis is found only on the observations I 3 (wap) and observation II 5(wap) with the average population of the observations I: 0,50 individuals and observations II: 0,80 individuals. While the populations Lygus sp. found in the observations I 3 (wap) to IV 9 (wap) with the average population of the observations I: 0.65 individuals, observations II: 1.10 individuals, observations III: 1.70 individuals, and observations IV: 1.40 individuals . Symptoms of N. tenuis is on the trunk and branches of the potato crop stylet puncture marks that are yellowish. While symptoms of Lygus sp. attack will not immediately apparent but will be visible after the leaves begin to open and enlarge.Keywords : Potato, Nesidiocoris tenuis, Lygus sp